Creative Economy Development Based on Local Wisdom and Technology in the Handicraft Sector - Sugisti, Irfani Afrilia; Nurhalila, Helliya Oktaviana; Hasymi, Moh Nurul; Ec. Gazali, Ec. Gazali; Rahman, Fadali (Civiliza Publishing, Indonesia., 2025)
The creative economy has become an important driver of economic growth while simultaneously supporting cultural preservation, particularly through the handicraft sector, which is deeply rooted in local wisdom. However, rapid technological development poses both opportunities and challenges for sustaining the cultural authenticity and competitiveness of handicraft products. This study aims to analyze the development of a creative economy based on local wisdom and technology in the handicraft sector. The research employed a qualitative approach using a literature review method. Data were collected from books, peer-reviewed journal articles, research reports, and official publications relevant to creative economy development, local wisdom, and technological integration. The collected data were analyzed descriptively and analytically by synthesizing key findings from previous studies. The results indicate that the handicraft sector contributes significantly to economic value creation, employment generation, and community empowerment. Local wisdom functions as a core cultural identity and competitive advantage that differentiates handicraft products in the market, while technology enhances production efficiency, design innovation, and market access through digital platforms. The integration of local wisdom and technology is identified as a strategic approach to achieving a competitive and sustainable creative economy. This study contributes conceptually by bridging cultural and technological perspectives in creative economy research and provides academic insights for policymakers and practitioners in developing culturally grounded and adaptive handicraft industries.